Interrelatedness of Brand Love and Brand Hate: The Case of a Female Personal Political Brand in Finland - Aro, Kaisa (Palgrave Macmillan, 2025)
The purpose of this study is to increase the understanding of two extreme brand relationships, namely brand love and brand hate, and their interrelatedness. This qualitative study employs abductive reasoning and naturally occurring, public, social media data. A political personal brand is chosen to represent an understudied, yet information-rich, context for both brand love and hate. This study shows that brand love and hate are conceptually close to each other and share several mechanisms, such as word of mouth (WOM), strong emotions and strong attitudes. Further, this study shows how these two brand relationships are publicly expressed in social media. This study provides guidance for brand managers in responding to expressions of brand love and hate and in understanding the interconnectivity between the underlying reasons customers express brand love and hate. Interestingly, this study shows how brand love and hate with a personal brand may have spill-over effects with organisations the personal brand presents and vice versa. The study contributes to the intersection of extreme brand relationships, personal branding and political branding.